Use of Propolis Extract as an Ingredient for Skin Cancer Cell Apoptosis Transfersome Cream with Gelatin as an Emulgator - Puspa, Galuh Wilujeng; Susilo, Agus; Cahyati, Miftakhul; Nurjannah, Nurjannah; Pranowo, Dodyk (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
Transfersome has been commonly used to increase the penetration of drugs derived from natural ingredients. Propolis is a natural ingredient with many benefits, such as antimicrobial, antiviral, anti-inflammatory, antitumor, antioxidant, and anticancer. In various in vitro studies, propolis showed proapoptotic activity in cancer cells. Gelatin is a chemical compound that can be used as an emulsifier because it has a hydrophobic part in the peptide chain. This study aimed to determine the optimal gelatin content based on physical tests as an emulsifier in the manufacture of emulsions for transfersome cream ingredients. The research method used was an experimental laboratory with 6 gelatin concentration treatments, namely 1% (P1), 2% (P2), 3% (P3), 4% (P4), 5% (P5), and 6% (P6) with 3 replicates. To make the emulsion, 5% propolis extract was added. The results of statistical analysis showed that the manufacture of emulsions using different concentrations of gelatin had a very significant effect (p